Beyond the division of multiple sclerosis into different subgroups: The Concept of Connectomopathy - Abdorreza Naser Moghadasi; Nasim Rezaeimanesh (Babol University of Medical Sciences, 2024)
Multiple Sclerosis (MS) pathophysiologically is a dynamic and progressive disease that involves all parts of central nervous system. This widespread involvement of the CNS has paved the way for proposing a new theory in MS in which MS is considered as a connectomopathy. Connectomopathy is a new concept describing the diseases in which not only the brain connectome is completely and extensively damaged, but the defective connectome itself can also become a breeding ground for the disease's progression. Connectomopathy provides a dynamic picture of MS. Since each person's connectome is unique to him/herself, so MS patients' connectomopathy varies from one to another. This variety not only challenges the classification of MS into different phenotypes, but also emphasizes the need for providing a personalized approach for the treatment of these patients.